Multilevel Prenatal Socioeconomic Determinants of Mexican American Children’s Weight: Mediation by Breastfeeding - Curci, Sarah G. (Health Psychol, 2020)
OBJECTIVE: Mexican American (MA) children are more likely to grow up in poverty than their non-Hispanic/Latinx white peers and are at an elevated risk for early onset obesity. The current study evaluated the effects of prenatal family- and neighborhood-level disadvantage on children’s weight and weight gain from 12 months through 4.5 years of age. Maternal breastfeeding duration was evaluated as a potential mechanism underlying the relation between multilevel disadvantage and weight. METHODS: Data was collected from 322 low-income, MA mother-child dyads. Women reported the degree of family socioeconomic disadvantage and breastfeeding status. Neighborhood disadvantage was evaluated with census-level metrics. Children’s weight and height were measured at laboratory visits. RESULTS: Greater prenatal neighborhood disadvantage predicted higher child Body Mass Index (BMI) at 12 months, over and above family-level disadvantage; this effect remained stable through 4.5 years. Breastfeeding duration partially mediated the effect of neighborhood disadvantage on child BMI. Breastfeeding duration predicted child BMI at all timepoints. CONCLUSIONS: Maternal prenatal residence in a neighborhood with high concentrated disadvantage may place low-income, MA children at increased risk of elevated weight status during the first few years of life. Breastfeeding duration emerged as potentially modifiable pathway through which the prenatal neighborhood impacts children’s early life weight.